2021
DOI: 10.1108/ijlma-04-2018-0082
|View full text |Cite
|
Sign up to set email alerts
|

Legal syncretism or the theory of unity in diversity as an alternative to legal pluralism in Indonesia

Abstract: Purpose Legal syncretism seeks to provide a rather different account of how laws interact with one another as the people deal with them. The purpose of this study is to provide a rather different account of how laws interact with one another as the people deal with them in the society. Design/methodology/approach This paper discusses the current concept of legal pluralism as to whether it really holds as the right theory for building a harmonious and trustworthy legal system in a multi-cultural country such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…However, the norms in the Perma do not regulate private legal entities at all. 40 On another consideration, the Supreme Court also uses conjunctions or phrases, the words "and" / "further" or "juncto", but these two phrases are not appropriate to use because the norm of Article 1 paragraph (4) of the Supreme Court Regulation Number 1 of 2011 is not a continuation of provisions governing private legal entities or the compilation of requirements to determine the legal standing of a private legal entity. The difference again occurs in the Supreme Court's Decision which does not consider the provisions of Article 1 paragraph (4) of Perma Number 1 of 2011 for applicants in the form of private legal entities.…”
Section: The Impact Of Norm Disharmony In Regulation Of Supreme Court...mentioning
confidence: 99%
“…However, the norms in the Perma do not regulate private legal entities at all. 40 On another consideration, the Supreme Court also uses conjunctions or phrases, the words "and" / "further" or "juncto", but these two phrases are not appropriate to use because the norm of Article 1 paragraph (4) of the Supreme Court Regulation Number 1 of 2011 is not a continuation of provisions governing private legal entities or the compilation of requirements to determine the legal standing of a private legal entity. The difference again occurs in the Supreme Court's Decision which does not consider the provisions of Article 1 paragraph (4) of Perma Number 1 of 2011 for applicants in the form of private legal entities.…”
Section: The Impact Of Norm Disharmony In Regulation Of Supreme Court...mentioning
confidence: 99%
“…Indonesia in the eyes of the world also ranks as the 14th largest country, with an area of 1,904,569 km2 with a population of 277.7 million as of January 2022. (Isra & Tegnan, 2021) Indonesia is bordered by a number of neighboring countries in Southeast Asia, the Australian continent, and Oceania.…”
Section: Introductionmentioning
confidence: 99%
“…The migration of people from different ethnicities, religions, cultures and social levels to Jakarta has made Jakarta the city with the highest population density in Indonesia. (Isra & Tegnan, 2021) In fact, it is the second most populous city in the world with a population of 35,363,000 after Tokyo as the first with a population of 39,105,000. However, when compared with the area; Jakarta (661.5 km²) while Tokyo (2,194 km²) of course it can be concluded that with a very large population and occupying an area that is 1/3 of the area of Tokyo, it can be concluded that the Jakarta area is really unhealthy and has a systemic impact from various factors.…”
Section: Introductionmentioning
confidence: 99%
“…This issue has been the object of various studies in the last two decades in Indonesia. Isra and Tegnan (2021) report the results of their research that the discourse of legal pluralism has not been able to help much in overcoming the difficulties faced by the pluralistic society in Indonesia, especially related to legal issues. The implication is that he offers syncretism as a more logical alternative to overcome this problem.…”
Section: Introductionmentioning
confidence: 99%